Calcium antagonists-induced lower urinary tract symptoms - Elhebir, Elsamaul Suliman A. (Curtin University, 2011)
Lower urinary tract symptoms (LUTS) are a group of obstructive and irritative urinary symptoms. These include storage, voiding, and post-micturition symptoms. LUTS are prevalent and bothersome in the rapidly growing ageing Australian population and they are associated with a significant deterioration in patients‟ quality of life (QoL). There are a number of risk factors for LUTS. These include medical conditions such as diabetes, stroke, Parkinson‟s disease along with some surgical procedures involving the pelvis or spinal cord. Ageing is also associated with structural and physiologic changes of the lower urinary tract which may contribute to LUTS. LUTS are often inappropriately thought of as a male only problem because of the high prevalence of benign prostatic hypertrophy (BPH) in older men; however, the development of LUTS is not gender specific and women may develop LUTS following menopause or post-hysterectomy.A number of drugs have been found to affect the bladder and the micturition process including the commonly prescribed calcium antagonists (CAs). CAs were the ninth most frequently prescribed group of drugs in Australia in the year 2008, with more than seven million prescriptions dispensed during that year. Apart for their effects relaxing the detrusor smooth muscle hence impairing micturition, CAs can also increase the production of urine through their natriuretic effect and cause constipation through their muscle relaxation and anti-cholinergic activity, which can further exacerbate LUTS. The association between CA use and LUTS is not well investigated. The aim of this research was to investigate the association between CA use and LUTS in males and females. Further to assess the consequences of CA-associated LUTS on users‟ QoL and receipt of treatment for LUTS.During the Phase 1 of this research, a review was conducted for all reports submitted to the Adverse Drug Reaction Advisory Committee (ADRAC) of Australia up until January 2009. The review revealed 80 reported cases (females 45 [56.2%], males 34 [42.5%]). The mean age of the patients was 63.4±14.1 years (range 36-99 years). Amlodipine was the most frequently reported drug and lercanidipine was the least reported. Pollakiuria and other obstructive urinary symptoms were the most commonly reported symptoms. More than half of the patients (46; 57.5%) had complete resolution of their LUTS after medication discontinuation while 10 (12.5%) patients did not recover; an outcome was not reported for the remaining 24 (30%) patients. The review highlighted the importance of including females and younger patients in future studies. Further, it also suggested that LUTS associated with CA use is reversible in the majority of cases following medication discontinuation.A study was conducted, in Phase 2 of this research, to investigate the relationship between CA-use and LUTS amongst hospitalised medical patients at Royal Perth Hospital. The study also looked at the impact of CA-associated LUTS on patients‟ urological QoL. A demographic questionnaire was used along with the validated International Prostate Symptoms Score (IPSS) -for measuring LUTS- and BPH Impact Index (BII) -for measuring urinary related QoL-. A total of 278 patients (151 males, 127 females, mean age 72.1±13.7 years) were recruited into the study. About one third of the patients were using CAs. The males mean IPSS of 12.2 ± 8.19 was higher compared to that of the females (9.74 ± 6.59, p = 0.007), indicating significantly worse LUTS. CA-users were found to have a statistically significantly higher mean IPSS (15.22 ± 8.1) compared to non-CA-users (9.25 ± 6.6, p < 0.0001). CA-users were found to be more likely to suffer from severe and moderate-to-severe LUTS (p < 0.0001 for both).The association between CA use and LUTS was not a class effect. A strong association emerged between amlodipine/nifedipine and diltiazem/verapamil use and severe LUTS, adjusted odds ratios (AOR) of 9.8 (95% CI, 3.98-24.34) and 8.2 (95% CI, 1.93-34.92), respectively. However, none of the patients receiving felodipine/lercanidipine suffered from severe LUTS. A similar association was also observed with moderate-to-severe LUTS.This increased risk of suffering from moderate and/or severe LUTS was matched by a similar deterioration of QoL measured by patients‟ level of dissatisfaction (AOR amlodipine/nifedipine 2.80 [95% CI, 1.68-4.68] and diltiazem/verapamil 3.65 [95% CI, 1.02-13.01]). The AOR was not statistically significant for felodipine/lercanidipine, 1.12 (95% CI, 0.47-2.67). Further, an estimated 22.4% of the CA-users group were taking medications to treat LUTS compared to 9.3% in the non-CA-users group, p = 0.003. Both male and female CA-users were three times more likely to be on an alpha-blocker than non-CA-users (p=0.0001). Male CA-users were two times more likely to have undergone urological surgeries (Fisher exact test, p=0.07) whilst female CA-users were nine times more likely (Fisher exact test, p=0.029).In Phase 3 of the research, a prescription sequence symmetry analysis was conducted in collaboration with the Department of Veteran affairs (DVA), Australia. This method was developed to create signals of a potential adverse event of drugs. The DVA prescription database for a 5-year period (2004-2008) was used to estimate the sequence ratio and the adjusted sequence ratio (ASR). The data revealed that there was about two-fold-increase in prazosin use after the first CA commencement, ASR 1.91 (95% CI 1.69-2.17). The use of urinary antispasmodics was also higher after CA use, ASR of 1.31 (95% CI 1.15-1.49). These results present a strong signal of an association between CA use and prazosin and urinary antispasmodic use (markers for LUTS).The final phase of the research involved an audit of dispensing records of 1,548 patients from a number of Australian residential aged care facilities (RACFs). In this study, CAs users were more likely to be on alpha blockers (as a group of drugs), AOR 2.11 (95% CI 1.05-4.26); and on prazosin, AOR 4.22 (95% CI 1.76-10.12). CA-users were also found to be more likely to be on urinary antispasmodics, AOR 2.18 (95% CI 1.32-3.61).The research had demonstrated a strong association between CA use and LUTS. This association could lead to a significant deterioration in QoL and it does not appear to be a class effect. CA-users are more likely to have more severe LUTS and to be on a treatment for LUTS or to have undergone urological interventions.xviiBased on these findings it is recommended that CA-users should be monitored for the development or the deterioration of LUTS. Moreover, CAs should always be considered as a possible cause for LUTS and consideration to be given to ceasing or switching CAs.